Sudan children of terror - Journeyman Pictures (United Kingdom : Journeyman Pictures, 2004)
Focused on terrorist training camps for children in Sudan. The children come from various countries such as Africa, Kenya, Nigeria and many others.
Keywords: Terrorism -- Sudan -- History; Children and terrorism